Mempertahankan Budaya Jawa di Daerah Transmigrasi Melalui Kesenian Kuda Lumping - Dwi Rahayu; Solfema Solfema; Lili Dasa Putri (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This article aims to examine the role of Kuda Lumping art as a medium to preserve Javanese culture in transmigration areas through a community empowerment approach in the cultural sector. Community empowerment in the context of culture aims to enhance the capacity, participation, and independence of communities in preserving and developing local traditions. Through Kuda Lumping art, Javanese communities in transmigration areas can not only safeguard their cultural identity but also utilize this tradition to support social and economic well-being. This literature study highlights the importance of collaboration between communities, the government, and cultural institutions in sustaining the Kuda Lumping tradition. By preserving and utilizing this tradition, Javanese communities can strengthen their cultural identity, maintain social harmony, and create new economic opportunities. Therefore, Kuda Lumping art holds a strategic role in preserving Javanese culture amidst the dynamics of transmigration communities.